2016
DOI: 10.1016/j.neuropharm.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent alterations in sleep/wake architecture elicited by the M4 PAM VU0467154 – Relation to antipsychotic-like drug effects

Abstract: Accumulating evidence indicates direct relationships between sleep abnormalities and the severity and prevalence of other symptom clusters in schizophrenia. Assessment of potential state-dependent alterations in sleep architecture and arousal relative to antipsychotic-like activity is critical for the development of novel antipsychotic drugs (APDs). Recently, we reported that VU0467154, a selective positive allosteric modulator (PAM) of the M4 muscarinic acetylcholine receptor (mAChR), exhibits robust APD-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 77 publications
3
30
0
Order By: Relevance
“…This is likely due to their different pharmacological profiles; they each act on multiple neurotransmitter systems in addition to dopamine, including serotonin, noradrenaline, and histamine (Miyamoto et al, 2005). Rodent studies have shown that antipsychotic drugs with different receptor selectivity have differential effects on sleep/wake states (Ongini et al, 1993;Gould et al, 2016).…”
Section: Effects Of Antipsychotic Medication On Sleep and Circadian Rmentioning
confidence: 99%
“…This is likely due to their different pharmacological profiles; they each act on multiple neurotransmitter systems in addition to dopamine, including serotonin, noradrenaline, and histamine (Miyamoto et al, 2005). Rodent studies have shown that antipsychotic drugs with different receptor selectivity have differential effects on sleep/wake states (Ongini et al, 1993;Gould et al, 2016).…”
Section: Effects Of Antipsychotic Medication On Sleep and Circadian Rmentioning
confidence: 99%
“…At 5 to 6 weeks of age, female Grm7 +/+ and Grm7 −/− mice were surgically implanted under isoflurane anesthesia with a telemetric transmitter (HD-X02; Data Sciences International [DSI], Minneapolis, MN) for recording EEG, electromyography (EMG) and motor activity as previously described. [18][19][20] Transmitters were implanted subcutaneously just off the midline of the dorsal flank of each mouse under aseptic conditions. Transmitter leads were tunneled subcutaneously to the skull.…”
Section: Surgerymentioning
confidence: 99%
“…Leveraging the PAM LY2033298, Conn and colleagues discovered a submicromolar PAM of acetylcholine, VU0152100, that was specific for the M4 receptor subtype 68 . Rounds of synthetic optimization led to PAMs that are more CNS penetrant and stable in vivo 69 and that have interesting new biology, including modulation of sleep– wake disturbances associated with schizophrenia. Meanwhile, a compound from Merck, MK-6884, is in phase I trials as a potential positron emission tomography (PET) ligand to assess occupancy of M4 PAMs in vivo (NCT02621606).…”
Section: Allosteric Ligands With New Biologymentioning
confidence: 99%